Mortality, Medical Complications, and Care Indicators Among Stroke Inpatients at King Abdulaziz Medical City-Jeddah-Saudi Arabia - Khayyat Waleed; Al Talhi Yousef; Alshareef Abdullah; Abou Elezz Ashraf; Halfawi Kareem; Alghamdi Saeed; Alhashemi Hashem (Journal of Neurological Research And Therapy, 2016)
Objective: To assess mortality, medical complications, and care indicators among stroke patients admitted to general medical units at King Abdulaziz Medical City-Jeddah-Saudi Arabia. Methods: This retrospective cohort study included all adult patients (>16 years) admitted to KAMC-Jeddah between January 1, 2014, and June 30, 2015, with acute stroke. Data regarding in-hospital stroke mortality and medical complications (pressure ulcer, pneumonia, venous thromboembolism dysphagia, and wheelchair dependency) and stroke care indicators (time-to-CT, carotid imaging, lipid profile, physical therapy, swallowing assessment, nutritional assessment, and length of stay) were collected. Results: Patients included were 208. Acute stroke mortality was 19%, while wheelchair dependency, and dysphagia on discharge were 39% and 56% respectively in general medical units. The incidence of pressure ulcers, pneumonia, and venous thromboembolism was 17%, 14%, and 3%, respectively. Pneumonia (odds ratio OR, 5.5; P = 0.002; 95% confidence interval CI, 1.9–16), abnormal troponin level (OR, 4.4; P = 0.002; 95% CI, 1.7–11),hemorrhagic stroke (OR, 3.9; P = 0.015; 95% CI, 1.3–12), and pressure ulcers (OR, 3.0; P = 0.036; 95% CI, 1.1–8.0) were significantly associated with increased mortality. Median time to CT scan was 117 minutes. Carotid imaging was performed for 67% of ischemic stroke patients, and 65% underwent fasting lipid profile assessment. Assessment by nutritionist, physiotherapist, and swallowing therapist was done for 90%, 76%, and 53% of stroke patients respectively. The median length of stay was 12 days. Conclusion: Acute stroke mortality was 19 %, while wheelchair dependency, and dysphagia on discharge were 39% and 56% respectively in general medical units at KAMC Jeddah. Pneumonia, abnormal troponin, hemorrhagic stroke, and pressure ulcers are associated with increased mortality. Future research is needed to compare outcomes of stroke care between general units and specialized stroke units nationally.
Keywords: Stroke